CFAVC scheme for high frequency series resonant inverter-fed domestic induction heating system. Issue 1 (2nd January 2016) - Nagarajan, Booma; Sathi, Rama Reddy
Abstract : This article presents the investigations on the constant frequency asymmetric voltage cancellation control in the AC–AC resonant converter-fed domestic induction heating system. Conventional fixed frequency control techniques used in the high frequency converters lead to non-zero voltage switching operation and reduced output power. The proposed control technique produces higher output power than the conventional fixed-frequency control strategies. In this control technique, zero-voltage-switching operation is maintained during different duty cycle operation for reduction in the switching losses. Complete analysis of the induction heating power supply system with asymmetric voltage cancellation control is discussed in this article. Simulation and experimental study on constant frequency asymmetric voltage cancellation (CFAVC)-controlled full bridge series resonant inverter is performed. Time domain simulation results for the open and closed loop of the system are obtained using MATLAB simulation tool. The simulation results prove the control of voltage and power in a wide range. PID controller-based closed loop control system achieves the voltage regulation of the proposed system for the step change in load. Hardware implementation of the system under CFAVC control is done using the embedded controller. The simulation and experimental results validate the performance of the CFAVC control technique for series resonant-based induction cooking system.